Boundary layer profile of decaying and non-decaying tropical storms near landfall - Tsui,EYL; Chan,PW; Toumi,R (Atmospheric Science Letters, 2024)
The vertical profile of the wind structure of translating tropical cyclones, including the associated azimuthal asymmetry, has been the subject of existing theoretical and observational studies using dropsondes. Most of these studies are based on data collected from relatively strong cyclones over the Atlantic. Here we explore the tropical cyclone boundary layer wind profile of mainly relatively weak landfalling cyclones near Hong Kong. We find that decaying tropical storms have a much larger mid- to low-level inflow angle than those that are intensifying or in steady-state. The inflow angles of intensifying, steady-state and decaying tropical storms converge towards the top of the boundary layer. The wind speed reduces through the boundary layer in a similar way in all three cases. The combination of these factors means that decaying tropical storms have stronger inflow than intensifying and steady-state ones. We attribute these local effects to remote enhanced surface friction over land when the storms are weakening.